HTML5 Step by Step (Step By Step (Microsoft)) - Wempen, Faithe (Microsoft Press, 2011)
Experience learning made easy—and quickly teach yourself how to create Web pages with the HTML5 specification. With Step by Step, you set the pace—building and practicing the skills you need, just when you need them!Use a division-based layout to structure your Web pagesInclude menu bars and hyperlinks for clear navigationApply colors, font sizes, and other formatting with CSSAdd graphics, sound, and video to your pagesUse the Canvas tag to render visual images on the flyBuild user-input forms with buttons, boxes, and menusYour Step by Step digital content includes:All the book's practice files—ready to download and put to work. See "Using the Practice Files," inside.Fully searchable online edition of this book—with unlimited access on the Web. Free online account required; see inside book.